Transformasi Ruang pada Rumah Pengrajin Gerabah di Desa Pagerjurang, Paseban, Bayat, Klaten - Azka Pintra; Dwita Hadi Rahmi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2021)
Title: Space Transformation in Pottery Craftsman’s House in Pagerjurang Village, Paseban, Bayat, Klaten The development of the city of Klaten from year to year has experienced rapidly, it affects all the districts in it, one of which is the Bayat district. Besides in Bayat is also a pottery and religious tourism village. Many people from outside the city visit here. This has made changes and developments in the houses in Bayat. Paseban Village is a village of pottery in Bayat and the majority of the population earns income as pottery artisans. Changes to the layout of the house in Paseban certainly have many factors that influence it. The pattern of home development in Paseban was not all the livelihoods of artisans. It is intended that there is a change in the function of space which was previously used as a dwelling only and now is changing into functions for making pottery. The existence of these changes wants to see what factors influence it. This study uses a qualitative deductive approach, where research is based on a theoretical foundation as a tool for field data collection. Researchers used questionnaires and interviews with Paseban villagers to obtain spatial transformation data. The current condition of the pottery craftsmen's house is seen from the physical form of the house is quite modern, but there are still houses that are still traditional. From interviews with the village head of Paseban, almost 90% have changed.